2017
DOI: 10.1186/s40949-017-0005-7
|View full text |Cite
|
Sign up to set email alerts
|

Stenting of the right ventricular outflow tract as primary palliation for Fallot-type lesions

Abstract: Background: To describe the institutional experience, technical aspects and outcome of stenting of the right ventricular outflow tract (RVOT) in the initial palliation of symptomatic patients with severely limited pulmonary blood flow. Methods: Retrospective case note and procedure review of patients undergoing stenting of the RVOT over a 10 year period at a quarternary institution. Patients: Between 2005 and 2014, 76 selected patients underwent cardiac catheterization with the aim to implant a stent into an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…In our study more than two thirds of the RVOTd procedures did not employ a stent, which would explain the much lower proportion of transannular patching (47% before matching, 68% after matching compared with 82% reported by Wilder et al and 100% by Sandoval et al , the latter using only stenting) 5 10. Quandt et al describe a large single centre experience with RVOT stenting in a variety of lesions, transannular patch usage being comparable to SPS 12. In our study we observed that using a balloon rather than a stent increases the risk of SPS placement afterwards due to inadequate pulmonary blood flow.…”
Section: Discussionsupporting
confidence: 47%
“…In our study more than two thirds of the RVOTd procedures did not employ a stent, which would explain the much lower proportion of transannular patching (47% before matching, 68% after matching compared with 82% reported by Wilder et al and 100% by Sandoval et al , the latter using only stenting) 5 10. Quandt et al describe a large single centre experience with RVOT stenting in a variety of lesions, transannular patch usage being comparable to SPS 12. In our study we observed that using a balloon rather than a stent increases the risk of SPS placement afterwards due to inadequate pulmonary blood flow.…”
Section: Discussionsupporting
confidence: 47%
“…10,16 Rates of re-intervention are not insignificant (65%) and higher than in previous studies in TOF (37.5%). 12 However, the aforementioned study contained all patients with TOF, and not only the cAVSD/TOF subset.…”
Section: Discussionmentioning
confidence: 99%
“…The cAVSD subset was identified as one of the lesions that required reintervention more frequently, as well as those of low weight, both possibly explaining the higher intervention rates in our cohort. 12 Furthermore, the weight and age of complete surgical repair is higher than in TOF alone, indicating a longer palliative period will likely lead to more reinterventions. 6 Our results are similar to that of Vitnova et al in that those who underwent a staged surgical repair were younger at the time of initial intervention and were more frequently cyanotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 More recently, catheter-based balloon valvuloplasty with or without RVOT stenting has been used as the initial palliation in neonates with TOF to improve arterial oxygen saturation and pulmonary arterial growth. 7 The timing of surgical repair has been controversial and evolving over the years. Before the 1970s, most patients with TOF underwent palliative surgery that involved the creation of a systemic-pulmonary shunt followed by delayed intra-cardiac repair.…”
Section: Patientsmentioning
confidence: 99%